Optical film with adhesive layer and image display device including optical film with adhesive layer
A thin circular polarized plate with controlled adhesive layer placement addresses reflection issues in image display devices by preventing bleaching and enhancing device flexibility and durability.
Patent Information
- Application Number
- JP2024199685
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-30
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing image display devices, particularly organic EL display devices, suffer from issues such as external light reflection and background reflection due to high reflective properties, which are not adequately addressed by conventional circular polarized plates, and there is a need for thinner polarized plates that do not degrade during cutting.
A thin circular polarized plate design with a controlled adhesive layer placement ensures that the phase difference layer is protected during cutting, using a specific configuration where the adhesive layer is positioned inward of the polarizer edge, and the phase difference layer is laminated with a protective layer to prevent exposure and bleaching.
This design effectively suppresses the bleaching of the polarized light, maintaining optical performance while allowing for thinner image display devices with improved flexibility and durability.
Smart Images

Figure 2025015694000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive layer-attached optical film and an image display device including the pressure-sensitive adhesive layer-attached optical film. [Background technology]
[0002] In recent years, image display devices such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) have rapidly become widespread. In organic EL display devices equipped with an organic EL panel, the organic EL panel has a highly reflective metal layer, which tends to cause problems such as external light reflection and background glare. It is known that these problems can be prevented by providing a circular polarizing plate including a λ / 4 plate on the viewing side (e.g., Patent Documents 1 to 3).
[0003] By using a λ / 4 plate having reverse wavelength dispersion characteristics as the circular polarizer, excellent anti-reflection characteristics can be realized. On the other hand, from the viewpoint of making image display devices thinner, there is a demand for making the circular polarizer thinner as well. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-311239 A [Patent Document 2] JP 2002-372622 A [Patent Document 3] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]
[0005] In order to make circular polarizing plates thinner, the inventors produced circular polarizing plates using thin λ / 4 plates. However, they found that the moisture permeability of the λ / 4 plates increased, and as a result, discoloration was more likely to occur at the edges than in conventional circular polarizing plates.
[0006] The present invention has been made to solve the above problems, and a main object of the present invention is to provide a thin optical film in which discoloration is suppressed. [Means for solving the problem]
[0007] Optical films such as circular polarizing plates are usually provided with a pressure-sensitive adhesive layer for laminating to an image display cell. As a result of intensive research to achieve the above object, the present inventors have found that when an optical film with a pressure-sensitive adhesive layer is cut into a desired shape, chipping occurs at the edge of the pressure-sensitive adhesive layer, exposing the retardation layer, which affects the decoloration of the polarizer, and have come up with the idea that the decoloration can be suppressed by controlling the chipping at the edge of the pressure-sensitive adhesive layer to within a predetermined range, thereby completing the present invention.
[0008] According to one aspect of the present invention, a polarizing plate including a polarizer and a protective layer disposed on at least one side of the polarizer, a retardation layer, and a pressure-sensitive adhesive layer are provided in this order from a viewing side, and the retardation layer has a moisture permeability of 300 g / m 2 The pressure-sensitive adhesive layer has a thickness of 24h or more, an end of the pressure-sensitive adhesive layer is located more inward than an end of the polarizer in cross-sectional view, and the horizontal distance between the end of the pressure-sensitive adhesive layer and the end of the polarizer is 0 μm to 50 μm. In one embodiment, the polarizing plate includes the polarizer and a protective layer disposed only on the viewing side of the polarizer. In one embodiment, the polarizer has a thickness of 10 μm or less. In one embodiment, the pressure-sensitive adhesive layer has a strain of 900% or less at a stress of 0.4 N when subjected to stress-strain measurement at 23°C. In one embodiment, the retardation layer includes a layer of a liquid crystal compound having a fixed orientation, and the Re(550) and Re(450) of the layer of a liquid crystal compound have a relationship of 0.8≦Re(450) / Re(550)<1. The Re(550) of the layer of a liquid crystal compound has a range of 100 nm to 190 nm. The angle between the slow axis of the layer of a liquid crystal compound and the absorption axis of the polarizer is 40° to 50°. According to one aspect of the present invention, there is provided an image display device comprising the pressure-sensitive adhesive layer-attached optical film. In one embodiment, the image display device is an organic electroluminescence display device. Effect of the Invention
[0009] According to the pressure-sensitive adhesive layer-attached optical film of the present invention, exposure of the retardation layer is suppressed, so that discoloration of the polarizer can be suppressed even when a thin retardation layer is used. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of a pressure-sensitive adhesive layer-attached optical film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a pressure-sensitive adhesive layer-attached optical film according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0012] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0013] A. Overall structure of the pressure-sensitive adhesive layer-attached optical film 1 is a schematic cross-sectional view of an adhesive layer-attached optical film according to one embodiment of the present invention. The adhesive layer-attached optical film 100A of the illustrated example has a polarizing plate 10, a retardation layer 20, and an adhesive layer 30 in this order from the viewing side. The polarizing plate 10 includes a polarizer 11, a protective layer (outer protective layer) 12 provided on the viewing side of the polarizer 11, and a protective layer (inner protective layer) 13 provided on the opposite side of the polarizer 11 from the viewing side. The protective layer 13 may be omitted depending on the purpose, etc. For example, when the retardation layer 20 can also serve as a protective layer for the polarizer 11, the protective layer 13 may be omitted.
[0014] 2 is a schematic cross-sectional view of a pressure-sensitive adhesive layer-attached optical film according to another embodiment of the present invention. The pressure-sensitive adhesive layer-attached optical film 100B of the illustrated example has a polarizing plate 10, a retardation layer 20, and a pressure-sensitive adhesive layer 30 in this order from the viewing side. The polarizing plate 10 includes a polarizer 11 and an outer protective layer 12, and the inner protective layer is omitted. In this embodiment, the retardation layer 20 has a laminated structure including a first retardation layer 20a and a second retardation layer 20b, and the retardation layer 20 (substantially the first retardation layer 20a) also serves as a protective layer for the polarizer 11. In a pressure-sensitive adhesive layer-attached optical film in which the inner protective layer is omitted, the polarizer is more likely to be decolored when the retardation layer is exposed compared to a pressure-sensitive adhesive layer-attached optical film in which an inner protective layer is provided, and therefore the effects of the present invention can be more suitably obtained.
[0015] In the embodiment of the present invention, the moisture permeability of the retardation layer 20 is 300 g / m 2 ·24h or more, and the end of the adhesive layer 30 is located inward from the end of the polarizer 11 in cross-sectional view. Here, "located inward" includes being at the same position, and allows the end of the adhesive layer 30 and the end of the polarizer 11 to be located on the same vertical line in cross-sectional view. More specifically, when the position of the end of the polarizer 11 is P1 and the position of the end of the adhesive layer 30 is P2 in cross-sectional view, P1 and P2 are on the same vertical line, or P2 is located inward from P1, and the distance (horizontal distance) D between P1 and P2 is 50 μm or less. The distance D between P1 and P2 is preferably short, and may be 0 μm to 40 μm, 0 μm to 35 μm, 0 μm to 30 μm, or 0 μm to 25 μm. By suppressing exposure of the end portion of the retardation layer 20 due to chipping of the adhesive layer 30 during cutting, discoloration of the polarizer 11 can be suppressed even when a retardation layer with high moisture permeability is used.
[0016] The retardation layer 20 and the polarizing plate 10 are typically bonded together via an adhesive layer such as an adhesive layer or a pressure-sensitive adhesive layer. In a cross-sectional view, the end of the adhesive layer is preferably located inward from the end of the polarizer. The distance (horizontal distance) between the end of the polarizer and the end of the adhesive layer is preferably short, and may be, for example, 0 μm to 50 μm, 0 μm to 40 μm, 0 μm to 35 μm, 0 μm to 30 μm, or 0 μm to 25 μm. By suppressing exposure of the polarizing plate due to chipping of the end of the adhesive layer, the effect of suppressing discoloration of the polarizer can be more suitably obtained. Note that, in a cross-sectional view, the end of the protective layer and the end of the retardation layer are preferably on the same vertical line as the end of the polarizer.
[0017] Although not shown, it is preferable that a release film is temporarily attached to the surface of the pressure-sensitive adhesive layer until the pressure-sensitive adhesive layer-attached optical film is used. The pressure-sensitive adhesive layer-attached optical film may further include other optical functional layers. The type, characteristics, number, combination, arrangement position, etc. of the optical functional layers that can be provided in the pressure-sensitive adhesive layer-attached optical film can be appropriately set according to the purpose.
[0018] The total thickness of the pressure-sensitive adhesive layer-attached optical film is preferably 120 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less. The lower limit of the total thickness may be, for example, 45 μm. The pressure-sensitive adhesive layer-attached optical film having such a total thickness can contribute to the thinning of the image display device and has excellent flexibility and bending durability, and therefore can be suitably applied to a curved image display device and / or a bendable or foldable image display device.
[0019] In one embodiment, the pressure-sensitive adhesive layer-attached optical film is a sheet-like film cut to a predetermined dimension. The pressure-sensitive adhesive layer-attached optical film according to the embodiment of the present invention has little chipping of the pressure-sensitive adhesive layer caused by shear stress during cutting, so that discoloration of the polarizer end portion after cutting into sheets can be suppressed. As a cutting method, any appropriate method such as punching, milling such as full-back processing, FFC processing, etc. can be adopted.
[0020] The components of the pressure-sensitive adhesive layer-attached optical film will be described in more detail below.
[0021] B. Polarizing plate B-1.Polarizer Any appropriate polarizer can be adopted as the polarizer 11. For example, the polarizer may be made of a single-layer resin film, or may be obtained by using a laminate of two or more layers.
[0022] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA)-based resin films, partially formalized PVA-based resin films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA and dehydrochlorinated polyvinyl chloride. A polarizer obtained by dyeing a PVA-based resin film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.
[0023] The dyeing with iodine is carried out, for example, by immersing the PVA-based resin film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based resin film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based resin film in water and washing it before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based resin film, and also to swell the PVA-based resin film and prevent uneven dyeing.
[0024] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In this embodiment, stretching typically includes immersing the laminate in an aqueous solution of boric acid to stretch it. Furthermore, stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous solution of boric acid. The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0025] The thickness of the polarizer is, for example, 25 μm or less, preferably 10 μm or less, and more preferably 8 μm or less, while the thickness of the polarizer is preferably 1 μm or more, more preferably 2 μm or more, and further preferably 3 μm or more.
[0026] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 43.0% to 46.0%, and preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.
[0027] B-2.Protective layer The outer protective layer 12 and the inner protective layer 13 (if present) are each composed of any suitable film that can be used as a protective layer for a polarizer. Typical materials for the inner protective layer 13 include cycloolefin resins such as polynorbornene, (meth)acrylic resins, polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin resins such as polyethylene, and polycarbonate resins. Typical examples of (meth)acrylic resins include (meth)acrylic resins having a lactone ring structure. Examples of (meth)acrylic resins having a lactone ring structure are described in, for example, JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, and JP-A-2005-146084. These publications are incorporated herein by reference. The inner protective layer 13 is preferably made of a cycloolefin resin. Representative materials for the outer protective layer 12 include cellulose resins such as triacetyl cellulose (TAC) and resins capable of forming a microporous film (e.g., polyurethane resins).
[0028] As described later, the pressure-sensitive adhesive layer-attached optical film can be disposed on the viewing side of an image display device (typically, an organic EL display device) so that the outer protective layer is the viewing side. Therefore, the outer protective layer may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, if necessary. In addition, the outer protective layer may be subjected to treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarization function, imparting an ultra-high phase difference), if necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the pressure-sensitive adhesive layer-attached optical film can be suitably applied to image display devices that can be used outdoors.
[0029] The thickness of the outer protective layer is preferably 10 μm to 80 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 50 μm. When a surface treatment is applied, the thickness of the outer protective layer includes the thickness of the surface treatment layer.
[0030] In one embodiment, the inner protective layer is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. The thickness of the inner protective layer is preferably 10 μm to 80 μm, more preferably 20 μm to 70 μm, and further preferably 30 μm to 50 μm.
[0031] C. Retardation layer The retardation layer 20 may be a single layer as shown in Fig. 1. The retardation layer 20 may also have a laminated structure of a first retardation layer 20a and a second retardation layer 20b as shown in Fig. 2, or may have a laminated structure of three or more layers.
[0032] The moisture permeability of the retardation layer (the moisture permeability of the entire laminate in the case of a laminate structure) is, for example, 300 g / m 2 - 24h or more, e.g. 350g / m 2 24h~700g / m 2 When a retardation layer having such a humidity is used, the effects of the present invention can be suitably obtained.
[0033] The thickness of the retardation layer (total thickness in the case of a laminated structure) can be appropriately set depending on the purpose. The thickness of the retardation layer is preferably 1 μm to 15 μm, more preferably 1 μm to 10 μm, and further preferably 2 μm to 8 μm. Even when such a thin retardation layer having high moisture permeability is used, discoloration of the edge of the polarizer can be suppressed, which is one of the features of the present invention.
[0034] When the retardation layer 20 is a single layer, the retardation layer can typically function as a λ / 4 plate. The retardation layer typically exhibits a refractive index characteristic of nx > ny = nz. The in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 120 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur.
[0035] The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, an organic EL display device having a very excellent reflection hue can be obtained.
[0036] The retardation layer preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. With such a configuration, very excellent antireflection characteristics can be realized.
[0037] The angle formed by the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°. If the angle is within such a range, by using the retardation layer as a λ / 4 plate as described above, an organic EL display device having very excellent antireflection characteristics can be obtained.
[0038] The retardation layer can be composed of any suitable material as long as it can satisfy the above characteristics. Specifically, the retardation layer may be an alignment solidification layer of a liquid crystal compound (hereinafter referred to as a liquid crystal alignment solidification layer), or may be a stretched film of a resin film.
[0039] When the retardation layer is a liquid crystal alignment solidified layer, the difference between nx and ny of the retardation layer obtained can be significantly increased compared to non-liquid crystal materials by using a liquid crystal compound, so that the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. As a result, the optical film with a pressure-sensitive adhesive layer (and, as a result, the image display device) can be made even thinner. In this specification, the term "alignment solidified layer" refers to a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. The term "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by hardening a liquid crystal monomer. In this embodiment, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the retardation layer (homogeneous alignment). Specific examples of liquid crystal compounds and details of the method for forming the liquid crystal alignment solidified layer are described in, for example, JP-A-2006-163343 and JP-A-2006-178389. The descriptions in these publications are incorporated herein by reference.
[0040] The thickness of the retardation layer constituted by a single layer of the liquid crystal alignment solidified layer can be, for example, 1 μm to 5 μm.
[0041] When the retardation layer 20 has a laminated structure of the first retardation layer 20a and the second retardation layer 20b, the first retardation layer is preferably a single layer that can function as a λ / 4 plate. The angle between the slow axis of the first retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°.
[0042] The second retardation layer may be a so-called positive C plate whose refractive index characteristics show the relationship nz>nx=ny. By using a positive C plate as the second retardation layer, it is possible to effectively prevent reflection in an oblique direction, and the anti-reflection function can be made to have a wide viewing angle. In this case, the retardation Rth(550) in the thickness direction of the second retardation layer is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the second retardation layer may be less than 10 nm.
[0043] The second retardation layer having a refractive index characteristic of nz>nx=ny may be formed of any appropriate material. The second retardation layer is preferably made of a film containing a liquid crystal material fixed in a homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method of forming the retardation layer include the liquid crystal compound and the method of forming the retardation layer described in
[0020] to
[0028] of JP-A-2002-333642. In this case, the thickness of the second retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0044] D.Adhesive layer As the adhesive layer, an adhesive layer that has relatively high elasticity and is less susceptible to adhesive chipping due to cutting processing is preferably used.
[0045] The pressure-sensitive adhesive layer has a strain of, for example, 900% or less, preferably 800% or less, more preferably 200% to 600%, and even more preferably 200% to 400% at a stress of 0.4 N when subjected to stress-strain measurement at 23°C.
[0046] The creep value of the pressure-sensitive adhesive layer at 85° C. may be preferably 80 μm or less, more preferably 1 μm to 60 μm, and even more preferably 1 μm to 50 μm. The creep value can be measured by the method described in the examples.
[0047] The storage modulus G' of the pressure-sensitive adhesive layer at 25°C is preferably 1.00 x 10 5 Pa or more, more preferably 1.10×10 5 Pa or more, and preferably 2.00×10 6 It may be less than Pa.
[0048] The storage modulus G' of the pressure-sensitive adhesive layer at 85°C is preferably 7.00 x 10 4 (Pa) or more, and more preferably 1.00×10 5 Pa or more, and more preferably 1.50×10 5 Pa or more, and preferably 5.50×10 6 It may be less than Pa.
[0049] The moisture permeability of the adhesive layer is, for example, 2500 g / m 2 - 24h or less, preferably 100g / m 2 24h~2000g / m 2 · It can be 24h.
[0050] The thickness of the pressure-sensitive adhesive layer is, for example, 5 μm to 50 μm, preferably 5 μm to 35 μm, and more preferably 5 μm to 25 μm.
[0051] Examples of the adhesive that forms the adhesive layer include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinylpyrrolidone-based adhesives, polyacrylamide-based adhesives, and cellulose-based adhesives. The adhesive base polymer is selected according to the type of adhesive. Among the adhesives, acrylic-based adhesives are preferably used because they have excellent optical transparency and adhesive properties.
[0052] The acrylic adhesive contains a (meth)acrylic polymer as a base polymer. The (meth)acrylic polymer usually contains an alkyl (meth)acrylate as a main component as a monomer unit. Note that (meth)acrylate means acrylate and / or methacrylate, and (meth) in this specification has the same meaning.
[0053] Examples of alkyl (meth)acrylates constituting the main skeleton of the (meth)acrylic polymer include linear or branched alkyl groups having 1 to 18 carbon atoms. These can be used alone or in combination. The average carbon number of these alkyl groups is preferably 3 to 9.
[0054] In addition, from the standpoint of adhesive properties, durability, adjustment of phase difference, adjustment of refractive index, etc., alkyl (meth)acrylates containing an aromatic ring, such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate, can be used as copolymerization monomers.
[0055] In order to improve adhesion and heat resistance, one or more types of copolymerizable monomers having a polymerizable functional group having an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group, can be introduced into the (meth)acrylic polymer by copolymerization. Specific examples of such copolymerizable monomers include hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methyl acrylate; (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, and the like. ) acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and other carboxyl group-containing monomers; acid anhydride group-containing monomers, such as maleic anhydride, itaconic anhydride, and other monomers; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers, such as styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamide 2-methylpropanesulfonic acid, (meth)acrylamide propanesulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, and other monomers containing a phosphoric acid group; and the like.
[0056] In addition, (N-substituted) amide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; alkylaminoalkyl(meth)acrylate monomers such as aminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and t-butylaminoethyl(meth)acrylate; alkoxyalkyl(meth)acrylate monomers such as methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; N-(meth)acryloyloxymethylene succinimide and N-(meth)acryloyloxymethylene succinimide; Examples of copolymerizable monomers include succinimide-based monomers such as acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyoctamethylene succinimide, and N-acryloylmorpholine; maleimide-based monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; and itaconimide-based monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide.
[0057] Further, as other copolymerization monomers, vinyl monomers such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, N-vinylcaprolactam, cyanoacrylate monomers such as acrylonitrile and methacrylonitrile, epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate, glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, silicone (meth)acrylate, and acrylic ester monomers such as 2-methoxyethyl acrylate can also be used. Further examples include isoprene, butadiene, isobutylene, and vinyl ether.
[0058] Further, as copolymerization monomers other than the above, there may be mentioned silane-based monomers containing silicon atoms, etc. Examples of the silane-based monomers include 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltriethoxysilane, 10-acryloyloxydecyltriethoxysilane, etc.
[0059] Furthermore, examples of copolymerizable monomers include tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol tetra ... Also usable are polyfunctional monomers having two or more unsaturated double bonds such as (meth)acryloyl groups, vinyl groups, etc., such as esters of (meth)acrylic acid and polyhydric alcohols, such as dipentaerythritol hexa(meth)acrylate and caprolactone-modified dipentaerythritol hexa(meth)acrylate, and polyester (meth)acrylates, epoxy (meth)acrylates, urethane (meth)acrylates, etc., in which two or more unsaturated double bonds such as (meth)acryloyl groups, vinyl groups, etc. are added as functional groups similar to those of the monomer components to the backbone of polyester, epoxy, urethane, etc.
[0060] The (meth)acrylic polymer contains alkyl (meth)acrylate as the main component in the weight ratio of all constituent monomers, and the ratio is preferably 70% by weight to 99.9% by weight, more preferably 75% by weight to 99% by weight, and further preferably 80% by weight to 98% by weight. By using alkyl (meth)acrylate as the main component, a pressure-sensitive adhesive having excellent adhesive properties can be obtained.
[0061] The weight ratio of the copolymerizable monomer in all the constituent monomers is preferably 0.1 to 30% by weight, more preferably 1 to 25% by weight, and further preferably 2 to 30% by weight.
[0062] Among these copolymerization monomers, hydroxyl group-containing monomers and carboxyl group-containing monomers are preferably used from the viewpoint of adhesiveness and durability. Hydroxyl group-containing monomers and carboxyl group-containing monomers can be used in combination. When the adhesive contains a crosslinking agent, these copolymerization monomers become reaction sites with the crosslinking agent. Hydroxyl group-containing monomers and carboxyl group-containing monomers are highly reactive with the intermolecular crosslinking agent, and are therefore preferably used to improve the cohesiveness and heat resistance of the resulting adhesive layer.
[0063] When a hydroxyl group-containing monomer is contained as a copolymerization monomer, the proportion is preferably 0.01 to 15% by weight, more preferably 0.05 to 10% by weight, and even more preferably 0.1 to 5% by weight. When a carboxyl group-containing monomer is contained as a copolymerization monomer, the proportion is preferably 0.01 to 15% by weight, more preferably 0.05 to 10% by weight, and even more preferably 0.1 to 5% by weight.
[0064] The weight-average molecular weight of the (meth)acrylic polymer is, for example, 1 million to 2.5 million, preferably 1.2 million to 2.3 million. A weight-average molecular weight of 1 million or more is preferable in terms of heat resistance. If the weight-average molecular weight is greater than 2.5 million, the adhesive may become hard. The weight-average molecular weight is measured by GPC (gel permeation chromatography) and calculated in terms of polystyrene.
[0065] Such a (meth)acrylic polymer can be produced by appropriately selecting a known production method such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The obtained (meth)acrylic polymer may be any of a random copolymer, a block copolymer, a graft copolymer, etc.
[0066] The adhesive forming the adhesive layer may contain a crosslinking agent according to the base polymer. When, for example, a (meth)acrylic polymer is used as the base polymer, an organic crosslinking agent or a polyfunctional metal chelate may be used as the crosslinking agent. Examples of the organic crosslinking agent include an isocyanate crosslinking agent, a peroxide crosslinking agent, an epoxy crosslinking agent, and an imine crosslinking agent. The polyfunctional metal chelate is a polyvalent metal covalently bonded or coordinately bonded to an organic compound. Examples of the polyvalent metal atom include Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, and Ti. Examples of the atom in the organic compound that is covalently bonded or coordinately bonded include an oxygen atom, and examples of the organic compound include an alkyl ester, an alcohol compound, a carboxylic acid compound, an ether compound, and a ketone compound.
[0067] The amount of the crosslinking agent used is preferably 0.5 to 6 parts by weight, more preferably 1 to 6 parts by weight, even more preferably 2 to 5.5 parts by weight, and even more preferably 3 to 5 parts by weight, relative to 100 parts by weight of the (meth)acrylic polymer.
[0068] The adhesive forming the adhesive layer can contain a silane coupling agent and other additives. For example, polyether compounds of polyalkylene glycols such as polypropylene glycol, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, reducing agents, antiaging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particles, foils, etc. can be added appropriately depending on the application. These additives are preferably used in an amount of 5 parts by weight or less, more preferably 3 parts by weight or less, and even more preferably 1 part by weight or less, per 100 parts by weight of the (meth)acrylic polymer.
[0069] E. Image display device The pressure-sensitive adhesive layer-attached optical film can be applied to image display devices such as organic EL display devices and liquid crystal display devices. Therefore, an embodiment of the present invention includes an image display device including the pressure-sensitive adhesive layer-attached optical film. When the image display device is an organic EL display device, the pressure-sensitive adhesive layer-attached optical film is laminated on the viewing side of the organic EL cell so that the retardation layer faces the organic EL cell. EXAMPLES
[0070] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified. (1) Thickness The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics, product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). (2) Stress-strain measurement The adhesive solution was cast onto the release-treated surface of a polyethylene terephthalate film (thickness: 38 μm) with one side treated for release, so that the thickness after drying would be approximately 4 μm. After heating and drying at 130 °C for 3 minutes, it was further aged at 50 °C for 24 hours, and then cut into pieces with a cross-sectional area of 1 mm 2 The specimen was placed in a tensile testing machine (Shimadzu Autograph AG-IS MS type, manufactured by Shimadzu Corporation) and pulled at a chuck distance of 10 mm, a pulling speed of 300 mm / min, and a temperature of 25°C. The maximum stress (N / mm 2 ) and maximum elongation (%) were measured. (3) Moisture permeability A sample obtained by bonding a retardation layer (a laminate of a first retardation layer and a second retardation layer) to a TAC film having a thickness of 25 μm via an adhesive was used as a measurement sample, and measurement was performed in accordance with JIS Z 0208 (cup method). (4) Creep value The optical film with adhesive layer was cut into a size of 10 mm x 30 mm to prepare a test sample. The upper end portion of the test sample, 10 mm x 10 mm, was attached to a SUS plate via the adhesive layer, and autoclaved for 15 minutes under conditions of 50°C and 5 atm. A precision hot plate installed so that the heating surface was vertical was heated to 85°C, and the SUS plate with the optical film with adhesive layer attached was installed so that the surface without the adhesive layer was in contact with the heating surface of the hot plate. After heating the SUS plate at 85°C for 5 minutes, a load of 500 gf was applied vertically downward to the lower end portion of the polarizing film with adhesive layer. The amount of deviation between the optical film with adhesive layer and the SUS plate was measured 1 second and 3600 seconds after the load was applied, and Cr1 and Cr 3600 Cr1 and Cr 3600 The creep value was determined as ΔCr by the following formula: ΔCr=Cr 3600 -Cr1 (5) Storage modulus The release film was peeled off from the adhesive layer produced in the manufacturing example, and multiple adhesive layers were laminated to produce a test sample with a thickness of approximately 1.5 mm. This test sample was punched out into a disk shape with a diameter of 7.9 mm, sandwiched between parallel plates, and dynamic viscoelasticity measurement was performed under the following conditions using Rheometric Scientific's "Advanced Rheometric Expansion System (ARES)," and the storage modulus G' was read from the measurement results. (Measurement conditions) Deformation mode: Torsion Measurement temperature: -40℃~150℃ Heating rate: 5℃ / min Measurement frequency: 1Hz (6) Single unit transmittance For a polarizing plate having a polarizer / protective layer structure, the transmittance Ts at wavelengths of 380 nm to 780 nm measured using a UV-Vis-NIR spectrophotometer (JASCO V-7100) was taken as the single transmittance Ts of the polarizer. This Ts is the Y value measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility.
[0071] [Production Example 1: Preparation of Adhesive Layer A] 1. Preparation of Adhesive A solution was prepared by adding 94.9 parts of butyl acrylate, 5 parts of acrylic acid, 0.1 parts of 2-hydroxyethyl acrylate, and 0.3 parts of 2,2'-azobisisobutyronitrile together with ethyl acetate to a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirrer. The solution was then stirred while blowing in nitrogen gas and reacted at 55°C for 8 hours to obtain a solution containing an acrylic polymer with a weight average molecular weight of 2.1 million. Ethyl acetate was then added to the solution containing the acrylic polymer to obtain an acrylic polymer solution with a solids concentration adjusted to 30%.
[0072] A pressure-sensitive adhesive solution was prepared by mixing, in this order, 4 parts of a crosslinking agent (manufactured by Nippon Polyurethane Co., Ltd., product name "Coronate L") whose main component is a compound having an isocyanate group and 0.2 parts of an epoxy group-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403") per 100 parts of the solid content of the acrylic polymer solution.
[0073] 2. Preparation of adhesive layer The above adhesive solution was applied to the surface of a release film made of a release-treated polyethylene terephthalate film (thickness 38 μm) and dried to a dry thickness of 20 μm, thereby preparing an adhesive layer A.
[0074] [Production Example 2: Preparation of Adhesive Layer B] Adhesive layer B was prepared in the same manner as in Production Example 1, except that the amount of crosslinking agent (manufactured by Nippon Polyurethane Co., Ltd., product name "Coronate L") added was 0.6 parts, and the adhesive solution was applied so that the thickness after drying was 15 μm.
[0075] [Production Example 3: Preparation of Adhesive Layer C] Adhesive layer C was produced in the same manner as in Production Example 1, except that 99 parts of butyl acrylate and 1 part of 4-hydroxybutyl acrylate were used as monomer components to obtain a solution containing an acrylic polymer having a weight average molecular weight of 1.8 million, 0.1 parts of trimethylolpropane / xylylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Takenate D110N") and 0.3 parts of peroxide crosslinking agent (manufactured by Nippon Oil & Fats Corporation, product name "Niper BMT") were used as crosslinking agents, and the adhesive solution was applied to a thickness of 15 μm after drying.
[0076] [Production Example 4: Preparation of Adhesive Layer D] Adhesive layer D was produced in the same manner as in Production Example 1, except that 99 parts of butyl acrylate and 1 part of 4-hydroxybutyl acrylate were used as monomer components to obtain a solution containing an acrylic polymer having a weight average molecular weight of 1.8 million, 0.02 parts of trimethylolpropane / xylylene diisocyanate adduct (manufactured by Tosoh Corporation, product name "Takenate D110N") and 0.3 parts of peroxide crosslinking agent (manufactured by Nippon Oil & Fats Corporation, product name "Niper BMT") were used as crosslinking agents, and the adhesive solution was applied to a thickness of 21 μm after drying.
[0077] [Production Example 5: Preparation of Adhesive Layer E] An adhesive layer E (thickness: 30 μm) was obtained in the same manner as in Production Example 3, except that the adhesive solution was applied so that the thickness of the resulting adhesive layer was 30 μm.
[0078] Viscoelasticity measurements were performed using the pressure-sensitive adhesive layers A to D produced in Production Examples 1 to 4. Additionally, the creep values of the pressure-sensitive adhesive layers were evaluated using pressure-sensitive adhesive layer-attached optical films (pressure-sensitive adhesive layer-attached optical films obtained in Examples 1 to 4 below) having the pressure-sensitive adhesive layers A to D. The results are shown in Table 1.
[0079] [Table 1]
[0080] [Example 1] 1. Preparation of Polarizer The thermoplastic resin substrate was a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of about 75° C. One side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER Z410") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution containing iodine and potassium iodide mixed together so that the iodine concentration was 0.03% by weight and the potassium concentration was 0.2% by weight) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizing film would be 42.0% (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4.0 wt %, potassium iodide 5.0 wt %) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds so that the total stretch ratio was 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, the laminate was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for approximately 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 5.2%. In this manner, a polarizer having a thickness of 5 μm was formed on the resin substrate.
[0081] 2. Preparation of Polarizing Plates The HC-TAC film was attached to the polarizer surface of the laminate of [resin substrate / polarizer] obtained above via a PVA-based resin aqueous solution. Specifically, a PVA-based resin aqueous solution (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFYMER (registered trademark) Z-200", resin concentration: 3% by weight) was applied, and the HC-TAC film was attached and heated for 5 minutes in an oven maintained at 60°C. The HC-TAC film was a film in which a hard coat (HC) layer (thickness 7 μm) was formed on a triacetyl cellulose (TAC) film (thickness 25 μm), and the TAC film was attached to the polarizer side. Next, the resin substrate was peeled off to obtain a polarizing plate having a configuration of [outer protective layer (HC-TAC film) / polarizer].
[0082] 3. Preparation of the first retardation layer 55 parts of the compound represented by formula (I), 25 parts of the compound represented by formula (II), and 20 parts of the compound represented by formula (III) were added to 400 parts of cyclopentanone (CPN), and then the mixture was heated to 60°C and stirred to dissolve. After dissolution was confirmed, the mixture was returned to room temperature, and 3 parts of Irgacure 907 (manufactured by BASF Japan Ltd.), 0.2 parts of Megafac F-554 (manufactured by DIC Corporation), and 0.1 parts of p-methoxyphenol (MEHQ) were added and further stirred to obtain a solution. The solution was transparent and uniform. The obtained solution was filtered through a 0.20 μm membrane filter to obtain a polymerizable composition. On the other hand, the polyimide solution for the alignment film was applied to a glass substrate having a thickness of 0.7 mm by spin coating, dried at 100°C for 10 minutes, and then baked at 200°C for 60 minutes to obtain a coating film. The obtained coating film was subjected to rubbing treatment to form an alignment film. The rubbing treatment was performed using a commercially available rubbing device. The polymerizable composition obtained above was applied to a substrate (substantially an alignment film) by spin coating, and dried at 100° C. for 2 minutes. After the obtained coating film was cooled to room temperature, it was irradiated with 30 mW / cm 2 of a high-pressure mercury lamp. 2 The liquid crystal alignment layer was irradiated with ultraviolet light at an intensity of 100 nm for 30 seconds to obtain a liquid crystal alignment layer (thickness 2.8 μm). The in-plane retardation Re(550) of the liquid crystal alignment layer was 130 nm. The Re(450) / Re(550) of the liquid crystal alignment layer was 0.851, and it showed reverse dispersion wavelength characteristics.
[0083] [ka] [ka]
[0084] 4. Preparation of the second retardation layer A liquid crystal coating liquid was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (IV) (the numbers 65 and 35 in the formula indicate the mol% of the monomer unit, and are conveniently represented as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. Then, the coating liquid was applied to a substrate film (norbornene-based resin film: manufactured by Nippon Zeon Co., Ltd., trade name "Zeonex") using a bar coater, and then the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. The liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, thereby forming an alignment solidified layer of the liquid crystal compound (liquid crystal alignment solidified layer, thickness 0.58 μm) that would become the second retardation layer on the substrate. This layer had Re(590) of 0 nm and Rth(590) of -100 nm, and exhibited refractive index characteristics of nz>nx=ny. [ka]
[0085] 5. Preparation of optical film with adhesive layer The first retardation layer was attached to the polarizer surface of the polarizing plate obtained in 2 through an adhesive (thickness 5 μm), and the glass substrate was peeled off. Here, the layers were attached so that the angle between the absorption axis of the polarizer and the slow axis of the first retardation layer was +45°. Next, the second retardation layer was attached to the surface of the first retardation layer through a UV-curable adhesive (thickness 1 μm), and the substrate film was peeled off. Furthermore, the adhesive layer A prepared in Production Example 1 was attached to the surface of the second retardation layer. This resulted in an adhesive layer-attached optical film (effectively an adhesive layer-attached circular polarizing plate) having a configuration of [protective layer / polarizer / first retardation layer / second retardation layer / adhesive layer A ( / release film)].
[0086] [Example 2] Except for using adhesive layer B instead of adhesive layer A, the same procedure as in Example 1 was followed to obtain an optical film with an adhesive layer having a structure of [protective layer / polarizer / first retardation layer / second retardation layer / adhesive layer B ( / release film)].
[0087] [Comparative Example 1] Except for using adhesive layer C instead of adhesive layer A, the same procedure as in Example 1 was followed to obtain an optical film with an adhesive layer having a structure of [protective layer / polarizer / first retardation layer / second retardation layer / adhesive layer C ( / release film)].
[0088] [Comparative Example 2] An optical film with a pressure-sensitive adhesive layer having a structure of [protective layer / polarizer / first retardation layer / second retardation layer / pressure-sensitive adhesive layer D ( / release film)] was obtained in the same manner as in Example 1, except that pressure-sensitive adhesive layer D was used instead of pressure-sensitive adhesive layer A.
[0089] [Comparative Example 3] Except for using adhesive layer E instead of adhesive layer A, the same procedure as in Example 1 was followed to obtain an optical film with an adhesive layer having a structure of [protective layer / polarizer / first retardation layer / second retardation layer / adhesive layer E ( / release film)].
[0090] [Reference example 1] 1. Preparation of Polarizer A polarizer having a thickness of 5 μm was formed on a resin substrate in the same manner as in Example 1, except that the iodine concentration in the dye bath was 0.025% by weight and the potassium concentration was 0.18% by weight.
[0091] 2. Preparation of Polarizing Plates A polarizing plate having a structure of [outer protective layer (HC-TAC film) / polarizer] was obtained in the same manner as in Example 1, except that the laminate of [resin substrate / polarizer] obtained above was used.
[0092] 3. Preparation of retardation film that constitutes the retardation layer 3-1.Polymerization of polyester carbonate resin Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane 29.60 parts by mass (0.046 mol), isosorbide (ISB) 29.21 parts by mass (0.200 mol), spiroglycol (SPG) 42.28 parts by mass (0.139 mol), diphenyl carbonate (DPC) 63.77 parts by mass (0.298 mol), and calcium acetate monohydrate 1.19×10 as a catalyst. -2 Part of mass (6.78×10 -5 mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets.
[0093] 3-2. Preparation of retardation film The obtained polyester carbonate resin (pellets) was melt-kneaded with 0.7 parts by mass of PMMA, and then vacuum-dried at 80°C for 5 hours. A long resin film having a thickness of 130 μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200 mm, setting temperature: 250°C), a chill roll (setting temperature: 120 to 130°C) and a winder. The obtained long resin film was stretched while adjusting so as to obtain a predetermined retardation, and a retardation film having a thickness of 38 μm was obtained. The stretching conditions were a stretching temperature of 143°C and a stretching ratio of 2.8 times in the width direction. The Re(550) of the obtained retardation film was 141 nm, Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12.
[0094] 4. Preparation of optical film with adhesive layer A retardation film was attached to the polarizer surface of the polarizing plate obtained in 2 through an adhesive (thickness 5 μm). Here, the film was attached so that the angle between the absorption axis of the polarizer and the slow axis of the retardation film was +45°. Next, the adhesive layer E prepared in Production Example 5 was transferred to the surface of the retardation film. This resulted in an optical film with an adhesive layer having a structure of [protective layer / polarizer / retardation layer / adhesive layer E ( / release film)].
[0095] <Cutting process> A laminate in which a surface protective film (manufactured by Nitto Denko Corporation, product name "PPF-100T") was laminated on the HC-attached TAC film side of the pressure-sensitive adhesive layer-attached optical film obtained in the Examples, Comparative Examples, and Reference Examples was used as the workpiece, and the end faces of each of the four rectangular sides were cut and ground by 2.5 mm using a full-back cutter under the following conditions, and cut into a rectangular shape of 25 mm x 50 mm. [Processing conditions] Rotation speed / feed speed: 4500rpm / 900mm / min
[0096] The obtained rectangular optical film with the pressure-sensitive adhesive layer was cut in the thickness direction, and the cross section was observed at a magnification of 10 times using an optical microscope (Olympus, MX61L), and the horizontal distance (amount of glue chipping) between the position P2 of the pressure-sensitive adhesive layer end and the position P1 of the polarizer end was measured. The results are shown in Table 2.
[0097] <Hot water test> The release film was peeled off from the rectangular optical film with adhesive layer obtained by cutting to expose the adhesive layer. The optical film with adhesive layer was attached to a glass plate via the adhesive layer, and immersed in warm water at 60°C for 30 minutes. The optical film with adhesive layer after immersion was observed under a microscope, and the depth of the area where decolorization occurred (amount of decolorization) was measured based on the end of the polarizer. In addition, taking into consideration the practical allowable range of the amount of decolorization, a decolorization amount of 250 μm or less was evaluated as "good", and a decolorization amount of more than 250 μm was evaluated as "poor". The results are shown in Table 2.
[0098] [Table 2]
[0099] As shown in Table 2, in the reference example in which the moisture permeability of the retardation layer was small, the discoloration of the polarizer was within the practically acceptable range even if the amount of glue chipping was large, but in the comparative example in which the moisture permeability of the retardation layer was large and the amount of glue chipping was also large, the amount of discoloration of the polarizer was large. On the other hand, in the example in which the amount of glue chipping was small, the discoloration of the polarizer was suppressed within the practically acceptable range even if the moisture permeability of the retardation layer was large. [Industrial Applicability]
[0100] The pressure-sensitive adhesive layer-attached optical film of the present invention is suitably used as a circular polarizing plate for image displays such as liquid crystal displays, organic EL displays, and inorganic EL displays. [Explanation of symbols]
[0101] 10 Polarizing plate 11 Polarizing film 12 Outer protective layer 13 Inner protective layer 20 Retardation layer 30 Adhesive layer 100 Optical film with adhesive layer
Claims
[Claim 1] A polarizing plate including a polarizer and a protective layer disposed on at least one side of the polarizer, a retardation layer, and a pressure-sensitive adhesive layer, in this order from a viewing side, The moisture permeability of the retardation layer is 300 g / m 2 ・24 hours or more, In a cross-sectional view, an end of the pressure-sensitive adhesive layer is located inward from an end of the polarizer, and a horizontal distance between the end of the pressure-sensitive adhesive layer and the end of the polarizer is 0 μm to 50 μm.
Citation Information
Patent Citations
Composite optical retardation plate, circularly polarizing plate and liquid crystal display, organic el display device
JP2002372622A
Apparatus for treating garbage
JP2003311239A
Retardation film and optical device using the same
JP3325560B2